Niobium-phosphorus co-doped nickel-cobalt-manganese lithium aluminate quaternary material, preparation method thereof and lithium ion battery using niobium-phosphorus co-doped nickel-cobalt-manganese lithium aluminate quaternary material

The quaternary material of nickel-cobalt-manganese-aluminate is prepared by co-doping niobium-phosphorus to form a core-shell structure, which solves the problem of structural phase change during the charging and discharge process, and improves the cycle stability and service life of the battery.

CN119905500APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311416159.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The quaternary material of nickel-cobalt manganese aluminate is prone to structural phase change during charging and discharging, resulting in microcracking, powdering and damage to the electrode structure, which in turn leads to the failure of lithium-ion batteries.

Method used

Niobium-phosphorus co-doping method is used to prepare nickel-cobalt-manganese-aluminate quaternary material. Through specific preparation steps and conditions, a material with a core-shell structure is formed. The niobium element is uniformly distributed, the phosphorus element is enriched on the particle surface and the particle size distribution is concentrated.

Benefits of technology

It improves the cyclic stability of the material, reduces structural distortion and collapse during charging and discharging, extends the service life of the battery, and reduces the difficulty of synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905500A_ABST
    Figure CN119905500A_ABST
Patent Text Reader

Abstract

The invention relates to a niobium-phosphorus co-doped nickel-cobalt-manganese lithium aluminate quaternary material, a preparation method thereof and a lithium ion battery using the niobium-phosphorus co-doped nickel-cobalt-manganese lithium aluminate quaternary material, and the method comprises the following steps: reacting a nickel-cobalt-aluminum ternary precursor prepared by a specific method with an aluminum-based hydrotalcite suspension containing transition metal elements and a niobium-containing compound, and then mixing and roasting with a lithium source to obtain the niobium-phosphorus co-doped nickel-cobalt-manganese lithium aluminate quaternary material. The niobium-phosphorus co-doped nickel cobalt manganese lithium aluminate quaternary material has a special structure, the niobium element is uniformly doped, the phosphorus element is enriched on the surface, the particle size distribution is relatively concentrated, and the lithium ion battery prepared by taking the niobium-phosphorus co-doped nickel cobalt manganese lithium aluminate quaternary material as the positive electrode material has relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of positive electrode materials for lithium-ion batteries, and in particular to a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material, a preparation method thereof, and a lithium-ion battery using the same. Background Art

[0002] Lithium Nickel Cobalt Manganese Aluminum Oxide LiNi 1-x-y-z Co x Mn y Al z As a quaternary positive electrode material, O2(NCMA) combines some advantages of NCM and NCA materials, and has the advantages of high specific capacity and good safety performance. However, when 1-xyz≥0.6, the battery is in the high voltage range (4.1-4.3V (vs.Li) during the charge and discharge process. + / Li)), nickel-cobalt-manganese-aluminum-lithium quaternary material will Structural phase change, after long-term and multiple cycles, microcracks appear in the material particles until the particles are pulverized, and the adverse side reactions with the electrolyte increase, the electrode structure is destroyed, and finally the battery fails. Starting from the crystal structure and material morphology is an effective way to improve the structural stability of high-nickel layered multi-element materials.

[0003] From the perspective of crystal structure, the method of co-doping metal-non-metal elements combines the advantages of two major types of doping elements, which can further improve the cycle performance of the material. Patent CN110085858A prepares the nickel-cobalt-manganese ternary precursor by conventional co-precipitation method, and then prepares the niobium-phosphorus co-doped nickel-cobalt-manganese ternary positive electrode material through two-step plasma calcination, which improves the structural stability of the material and reduces the residual alkali on the surface. However, the co-precipitation synthesis method of nickel-cobalt-aluminum ternary has strict requirements on reaction conditions. In addition, this method adopts conventional co-precipitation method to prepare ternary precursor, plasma-enhanced rotary furnace and other professional equipment, which has high equipment requirements and is not conducive to industrial production. Moreover, it is only subjected to simple surface coating and calcination, which is not conducive to the diffusion of doped ions in the ternary material. This problem is also difficult to solve in the nickel-cobalt-manganese-aluminum quaternary system.

[0004] From the perspective of material morphology, a "core-shell" or "gradient" secondary spherical precursor with high nickel and low manganese in the core and low nickel and high manganese in the outer layer is usually constructed, and then lithiated and fired to obtain a finished material that inherits the structural characteristics. However, the synthesis efficiency of "core-shell" or "gradient" quaternary materials distinguished by transition metal concentration is low and difficult, and is not suitable for large-scale production. Summary of the invention

[0005] The purpose of the present disclosure is to provide a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material, a preparation method thereof, and a lithium ion battery using the same. The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method of the present disclosure has a core-shell structure, the niobium element is evenly distributed, the phosphorus element is enriched on the particle surface, and the particle size distribution is concentrated. When used as a positive electrode material for a lithium ion battery, good cycle stability can be obtained.

[0006] In order to achieve the above-mentioned object, the present disclosure provides, in a first aspect, a method for preparing a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material, the method comprising the following steps:

[0007] (1) contacting a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to react and obtain a first pre-product;

[0008] (2) subjecting the first pre-product and the lithium-containing compound to a first ball milling, and then subjecting the obtained mixture to a first heat treatment in a first oxygen-containing atmosphere to obtain a second pre-product;

[0009] (3) subjecting the second pre-product and the first phosphorus-containing compound to a second ball milling;

[0010] (4) subjecting the third pre-product obtained in step (3) and the second phosphorus-containing compound to a second heat treatment under an inert atmosphere;

[0011] (5) subjecting the fourth pre-product obtained in step (4) to a third heat treatment in a second oxygen-containing atmosphere;

[0012] Wherein, the aluminum-based hydrotalcite contains a transition metal element, the transition metal element is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1;

[0013] The method for preparing the nickel-cobalt-manganese ternary precursor comprises the following steps:

[0014] S01. Adding a reaction base liquid to a primary reactor, wherein the reaction base liquid comprises water, an alkaline solution and an ammonia complexing liquid, and the amount of the reaction base liquid added is 30%-80% of the effective volume of the primary reactor;

[0015] S02. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the primary reactor, and when the primary reactor is full, the material in the primary reactor is concentrated, and the concentrated solution is refluxed into the primary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 3-4 times the effective volume of the primary reactor, and the material in the primary reactor is transferred to the secondary reactor;

[0016] S03. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the secondary reactor, and when the secondary reactor is full, the material in the secondary reactor is concentrated, and the concentrated solution is refluxed into the secondary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 2-3 times the effective volume of the secondary reactor, and the material in the secondary reactor is transferred into the tertiary reactor;

[0017] S04. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, the alkaline solution and the ammonia complex solution are continuously introduced into the tertiary reactor, and when the tertiary reactor is full, the material in the tertiary reactor is concentrated, and the concentrated solution is refluxed into the tertiary reactor until the D50 particle size of the particles in the tertiary reactor is 9-11 μm;

[0018] In step S01, when adding the reaction base solution, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-5 g / L;

[0019] In step S02, before the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-4.5 g / L; after the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 10.7-11.0 and the NH3 concentration is 3-4 g / L;

[0020] In step S03, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the secondary reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L;

[0021] In step S04, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the three-stage reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L.

[0022] Optionally, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b (OH)2, where 0 <a≤0.1,0<b≤0.1。

[0023] Optionally, in step (1), the molar ratio of the transition metal element in the aluminum-based hydrotalcite to the niobium element in the niobium-containing compound is greater than 2:1.

[0024] Optionally, the niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate;

[0025] The lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate;

[0026] The first phosphorus-containing compound includes one or more of ammonium phosphate, diammonium hydrogen phosphate and diammonium dihydrogen phosphate;

[0027] The second phosphorus-containing compound includes phosphite and / or hypophosphite;

[0028] Optionally, the phosphite includes sodium phosphite and / or ammonium phosphite, and the hypophosphite includes sodium hypophosphite and / or ammonium hypophosphite;

[0029] The molar ratio of the first phosphorus-containing compound to the second pre-product is (0.5-4):100;

[0030] The molar ratio of the second phosphorus-containing compound to the third pre-product is 1:(2-50).

[0031] Optionally, the average particle size of the niobium-containing compound is 50-80 nm, the average particle size of the lithium-containing compound is 6-8 μm, and the average particle size of the first phosphorus-containing compound is 5-10 μm.

[0032] Optionally, the molar ratio of the total molar sum of nickel, cobalt, manganese, aluminum and niobium in the first pre-product to the lithium in the lithium-containing compound is 1:(1.0-1.1).

[0033] Optionally, in step (2), the first heat treatment comprises the following steps:

[0034] a. Raise the temperature to 300-400°C at a heating rate of 1-8°C / min for the first calcination for 1-3h;

[0035] b. Continue heating to 450-500°C at a heating rate of 1-8°C / min and perform a second calcination for 1-3h;

[0036] c. Continue heating to 700-800°C at a heating rate of 2-6°C / min for the third calcination for 10-15h;

[0037] d. Cool down to 300-400℃ at a cooling rate of 1-3℃ / min, and then cool to below 100℃.

[0038] Optionally, step (4) is carried out in a tube furnace, the second phosphorus-containing compound is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace.

[0039] Optionally, in step (4), the second heat treatment method includes calcination, and the second heat treatment conditions include a temperature of 200-400° C. and a time of 1-5 h;

[0040] In step (5), the third heat treatment method includes roasting, and the third heat treatment conditions include: temperature of 600-850°C and time of 3-8h.

[0041] Optionally, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere;

[0042] The first oxygen-containing atmosphere and the second oxygen-containing atmosphere are the same or different, and are independently an oxygen atmosphere or an air atmosphere.

[0043] Optionally, the time for the first ball milling and the second ball milling is 1-4 hours respectively.

[0044] Optionally, the mixed salt solution contains nickel ions, cobalt ions and manganese ions, and the total molar concentration of the nickel ions, the cobalt ions and the manganese ions is 1.8-2.5 mol / L.

[0045] Optionally, the alkaline solution comprises a sodium hydroxide solution and / or a potassium hydroxide solution, wherein OH - The concentration is 5-10 mol / L;

[0046] The ammonia complex solution includes aqueous ammonia, and the mass fraction of NH3 in the ammonia complex solution is 15-22%.

[0047] Optionally, in the primary reactor, the secondary reactor and the tertiary reactor, the reaction temperature is 50-65° C., the stirring speed is 100-400 rpm, and the oxygen content is less than 0.01% by volume.

[0048] Optionally, the effective volume of the secondary reactor is 3-4 times the effective volume of the primary reactor, and the effective volume of the tertiary reactor is 3-4 times the effective volume of the secondary reactor.

[0049] A second aspect of the present disclosure provides a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method described in the first aspect of the present disclosure.

[0050] Optionally, the quaternary material is a particle comprising a core and a shell layer coated outside the core;

[0051] The diameter distance of the particles is less than 0.67.

[0052] Optionally, A Nb With D Nb The ratio is 0.9-1.1, AP With D P The ratio is 5-15;

[0053] Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus on the surface of the particles, A Nb represents the molar ratio of niobium element on the surface of the particle, A P represents the molar percentage of phosphorus on the surface of the particle;

[0054] Based on the total molar mass of nickel, cobalt, manganese, aluminum, niobium and phosphorus in the bulk phase of the particles, D Nb represents the molar ratio of niobium element in the bulk phase of the particle, D P It represents the molar percentage of phosphorus element in the bulk phase of the particles.

[0055] Optionally, the quaternary material includes a chemical formula of LiNi x Co y Mn z Al w Nb n P m Particles of O2, 0.7<x<1, 0<y<0.2, 0<z<0.1, 0<w<0.05, 0.002<n<0.02, 0.001<m<0.02.

[0056] A third aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material described in the second aspect of the present disclosure.

[0057] Through the above technical scheme, the present disclosure adopts a nickel-cobalt-aluminum ternary precursor prepared by a specific method to react with an aluminum-based hydrotalcite suspension containing transition metal elements and a niobium-containing compound, and then mixes with a lithium source and roasts it, and finally obtains a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material through phosphorus doping. The above quaternary material has a core-shell structure and a more complete crystal structure, which alleviates the intercrystalline stress caused by volume deformation during charging and discharging; the microcracks caused by multiple cyclic phase changes are also less, further improving the cycle performance of the battery; and the method disclosed in the present disclosure can reduce the difficulty of synthesizing the quaternary material, the niobium element in the prepared quaternary material is evenly distributed, the phosphorus element is enriched on the surface of the material, and the diameter distance is small, and the particle size distribution is relatively concentrated. Using it as a positive electrode material for a lithium ion battery can further improve the cycle performance of the material.

[0058] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0060] Figure 1 is a scanning electron microscope image of the quaternary material A1 prepared in Example 1 of the present disclosure;

[0061] Figure 2 It is a scanning electron microscope image of the quaternary material D6 prepared in comparative example 6 of the present disclosure. DETAILED DESCRIPTION

[0062] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0063] The first aspect of the present disclosure provides a method for preparing a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material, the method comprising the following steps:

[0064] (1) contacting a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to react and obtain a first pre-product;

[0065] (2) subjecting the first pre-product and a lithium-containing compound to a first ball milling, and then subjecting the obtained mixture to a first heat treatment in a first oxygen-containing atmosphere to obtain a second pre-product;

[0066] (3) subjecting the second pre-product and the first phosphorus-containing compound to a second ball milling;

[0067] (4) subjecting the third pre-product obtained in step (3) and the second phosphorus-containing compound to a second heat treatment under an inert atmosphere;

[0068] (5) subjecting the fourth pre-product obtained in step (4) to a third heat treatment in a second oxygen-containing atmosphere;

[0069] Wherein, the aluminum-based hydrotalcite contains a transition metal element, the transition metal element is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1;

[0070] The method for preparing the nickel-cobalt-manganese ternary precursor comprises the following steps:

[0071] S01. Adding a reaction base liquid to a primary reactor, wherein the reaction base liquid comprises water, an alkaline solution and an ammonia complexing liquid, and the amount of the reaction base liquid added is 30%-80% of the effective volume of the primary reactor;

[0072] S02. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the primary reactor, and when the primary reactor is full, the material in the primary reactor is concentrated, and the concentrated solution is refluxed into the primary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 3-4 times the effective volume of the primary reactor, and the material in the primary reactor is transferred to the secondary reactor;

[0073] S03. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the secondary reactor, and when the secondary reactor is full, the material in the secondary reactor is concentrated, and the concentrated solution is refluxed into the secondary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 2-3 times the effective volume of the secondary reactor, and the material in the secondary reactor is transferred into the tertiary reactor;

[0074] S04. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, the alkaline solution and the ammonia complex solution are continuously introduced into the tertiary reactor, and when the tertiary reactor is full, the material in the tertiary reactor is concentrated, and the concentrated solution is refluxed into the tertiary reactor until the D50 particle size of the particles in the tertiary reactor is 9-11 μm;

[0075] In step S01, when adding the reaction base solution, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-5 g / L;

[0076] In step S02, before the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-4.5 g / L; after the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 10.7-11.0 and the NH3 concentration is 3-4 g / L;

[0077] In step S03, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the secondary reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L;

[0078] In step S04, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the three-stage reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L.

[0079] In the present disclosure, the reaction of the suspension containing aluminum-based hydrotalcite with the nickel-cobalt-manganese ternary precursor and the niobium-containing compound in step (1) belongs to liquid phase coating, which has a better coating effect than the dry ball milling using hydrotalcite nanosheets directly, and the particle size distribution of the prepared quaternary material is more concentrated, and has better electrochemical performance, especially cycle stability; during the heat treatment process, the cobalt element or nickel element in the aluminum-based hydrotalcite can drive the niobium element into the material through the "cooperative diffusion effect", reducing the difficulty of material synthesis. And the strong chemical bond of Nb-O can be used to inhibit the structural distortion and structural collapse of the material during the charge and discharge process, and improve the cycle stability of the material. The phosphorus element is mainly enriched on the surface of the particles, which can not only reduce the surface structure damage caused by the water washing and alkali reduction process, but also play a coating effect to alleviate the corrosion of the electrolyte to the material. In the method disclosed in the present invention, phosphorus doping is performed by solid phase diffusion and vapor phase deposition, which is effective in improving the phosphorus doping effect in the bulk phase of the material and the phosphorus enrichment effect on the surface. Multiple phosphorus doping methods work synergistically. In addition, the particle size distribution of the quaternary material prepared by the method disclosed in the present invention is relatively concentrated, which can further improve the cycle performance of the material.

[0080] According to one embodiment of the present disclosure, in step (1), the molar ratio of the transition metal element in the aluminum-based hydrotalcite to the niobium element in the niobium-containing compound is greater than 2:1. Meeting the above ratio can reduce the content of niobium element on the surface, so that the prepared material has better electrochemical properties.

[0081] In the present disclosure, in step (1), the feed amounts of aluminum-based hydrotalcite, nickel-cobalt-manganese ternary precursor and niobium-containing compound are LiNi x Co y Mn z Al w Nb n P m The molar ratio of Ni, Co, Mn, Al and Nb in the O2 material can be weighed to meet the molar content of Ni, Co, Mn, Al and Nb in the final product.

[0082] According to one embodiment of the present disclosure, in step (2), the molar ratio of the total molar sum of nickel, cobalt, manganese, aluminum and niobium in the first pre-product to the lithium in the lithium-containing compound is 1:(1.0-1.1) and preferably 1:(1.02-1.08).

[0083] According to one embodiment of the present disclosure, in step (2), the first heat treatment comprises the following steps:

[0084] a. Raise the temperature to 300-400°C at a heating rate of 1-8°C / min for the first calcination for 1-3h;

[0085] b. Continue heating to 450-500°C at a heating rate of 1-8°C / min and perform a second calcination for 1-3h;

[0086] c. Continue heating to 700-800°C at a heating rate of 2-6°C / min for the third calcination for 10-15h;

[0087] d. Cooling to 300-400°C at a cooling rate of 1-3°C / min, and then cooling to below 100°C. The cooling method may be furnace cooling, for example;

[0088] The above-mentioned heat treatment method can make the pre-product and the lithium-containing compound fully decompose into oxides in the first and second calcination stages, improve the solid phase reaction efficiency in the third calcination stage, and generate a quaternary material with a more complete crystal form and a more concentrated particle size distribution; after the calcination is completed, the stress between the grains is at least partially eliminated through annealing treatment, thereby improving the cyclic stability of the quaternary material.

[0089] In the present disclosure, in order to remove surface impurities, step (4) further comprises: cooling the solid material obtained by the second heat treatment to room temperature, adding it to water, stirring and washing for 10 minutes, filtering and drying to obtain a fourth pre-product. The drying method is conventional in the art and is not specifically required here.

[0090] According to one embodiment of the present disclosure, the niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate, and when the niobium-containing compound includes more than two kinds, their proportion is not limited; the lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate, and when the lithium-containing compound includes more than two kinds, their proportion is not limited; the first phosphorus-containing compound includes one or more of ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate, and when the first phosphorus-containing compound includes more than two kinds, their proportion is not limited; the second phosphorus-containing compound includes phosphite and / or hypophosphite; further, the phosphite includes sodium phosphite and / or ammonium phosphite; the hypophosphite includes sodium hypophosphite and / or ammonium hypophosphite, and when the second phosphorus-containing compound includes more than two kinds, their proportion is not limited.

[0091] According to one embodiment of the present disclosure, the molar ratio of the first phosphorus-containing compound to the second pre-product is (0.5-4):100; preferably (1-2):100.

[0092] According to one embodiment of the present disclosure, the molar ratio of the second phosphorus-containing compound to the third pre-product is 1:(2-50); preferably 1:(5-20).

[0093] According to one embodiment of the present disclosure, the average particle size of the niobium-containing compound is 50-80 nm, preferably 50-60 nm; the average particle size of the lithium-containing compound is 6-8 μm, preferably 6-7 μm; the average particle size of the first phosphorus-containing compound is 5-10 μm, preferably 5-8 μm.

[0094] According to an embodiment of the present disclosure, both the first ball milling and the second ball milling are solid phase ball milling. Further, the time of the first ball milling and the second ball milling is 1-4 hours respectively. Meeting the above ball milling time can ensure sufficient coating and avoid the precursor particles from being broken due to excessive ball milling time.

[0095] According to one embodiment of the present disclosure, step (4) is carried out in a tubular furnace, the second phosphorus-containing compound is placed upstream of the tubular furnace, and the third pre-product is placed downstream of the tubular furnace. The upstream and downstream are relatively arranged along the second phosphorus-containing compound, the second phosphorus-containing compound located upstream decomposes under high temperature, and the gaseous phosphide flows to the downstream to react with the third pre-product. By using the above method, phosphorus elements are doped into the quaternary material lattice by solid phase diffusion and enriched on the surface of the quaternary material particles by vapor deposition, thereby improving the structure and surface stability of the material.

[0096] According to one embodiment of the present disclosure, in step (4), the second heat treatment method includes roasting, and the conditions of the second heat treatment include: temperature of 200-400°C, time of 1-5h; preferably, temperature of 300-400°C, time of 2-4h; in step (5), the third heat treatment method includes roasting, and the conditions of the third heat treatment include: time of 600-850°C, time of 3-8h; preferably, temperature of 700-800°C, time of 3-5h.

[0097] According to one embodiment of the present disclosure, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0098] According to an embodiment of the present disclosure, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are the same or different, and are independently oxygen atmosphere or air atmosphere. Specifically, the first oxygen-containing atmosphere and the second oxygen-containing atmosphere are both oxygen atmospheres, for example.

[0099] In the present disclosure, the definitions of nitrogen atmosphere, argon atmosphere, oxygen atmosphere, and air atmosphere are conventional in the art.

[0100] According to one embodiment of the present disclosure, a method for preparing a suspension containing aluminum-based hydrotalcite comprises the following steps:

[0101] S1 preparing a first solution comprising a transition metal source and an aluminum source;

[0102] S2: adding the first solution and the alkaline solution into the colloid mill at a rotation speed of 1000-3000 r / min for 2-5 min to obtain a suspension.

[0103] In the present disclosure, the transition metal source can be, for example, a soluble salt of a transition metal, preferably including one or more of nickel sulfate, nickel chloride, nickel nitrate and nickel acetate; or, the soluble transition metal salt includes one or more of cobalt sulfate, cobalt chloride, cobalt nitrate and cobalt acetate; when the transition metal source includes more than two types, there is no specific limitation on their ratio.

[0104] In the present disclosure, the aluminum source includes one or more of aluminum sulfate, aluminum chloride, aluminum nitrate and aluminum acetate; when the aluminum source includes two or more, the ratio thereof is not specifically limited.

[0105] In the present disclosure, the alkaline solution comprises a soluble alkali and a soluble alkaline salt, wherein the soluble alkali comprises sodium hydroxide and / or potassium hydroxide; the soluble alkaline salt comprises sodium carbonate and / or potassium carbonate; specifically, the soluble alkali may be sodium hydroxide, and the soluble alkaline salt may be sodium carbonate. Further, the concentration of the soluble alkali is 1-2 mol / L, and the concentration of the soluble alkaline salt is 0.25-0.75 mol / L.

[0106] In the present disclosure, the volume ratio of the first solution to the alkaline solution is (0.8-1.5):1; for example, they can be mixed in equal volumes.

[0107] In the present disclosure, the molar ratio of the transition metal source calculated as transition metal element to the aluminum source calculated as aluminum element is (2-5):1; the total molar concentration of the transition metal source calculated as transition metal element and the aluminum source calculated as aluminum element is 0.5-1.25 mol / L.

[0108] According to one embodiment of the present disclosure, step (1) comprises: mixing a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound, and then aging the mixture in a water bath at 95-98°C for 2-4 hours, performing solid-liquid separation on the mixed material obtained by aging, and washing the obtained solid until the pH value of the washing liquid is below 7.5; then drying the washed solid at 80-120°C for 8-12 hours to obtain a first pre-product; wherein the solid-liquid separation method is conventional in the art, for example, it can be filtration; and the drying method is conventional in the art.

[0109] In the present disclosure, pH values ​​are all tested values ​​under 25°C and normal pressure conditions.

[0110] According to one embodiment of the present disclosure, the chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b(OH)2, where 0 <a≤0.1,0<b≤0.1。

[0111] According to one embodiment of the present disclosure, the D50 particle size of the nickel-cobalt-manganese ternary precursor is 9-11 μm, preferably 9.5-10.5 μm.

[0112] In the present disclosure, the mixed salt solution can be selected within a certain range. For example, the mixed salt solution contains nickel ions, cobalt ions and manganese ions, and the total molar concentration of nickel ions, cobalt ions and manganese ions can be 1.8-2.5 mol / L; the molar ratio of nickel ions, cobalt ions and manganese ions in the mixed salt solution can be, for example, the same as the molar ratio of nickel element, cobalt element and manganese element in the nickel-cobalt-manganese ternary precursor.

[0113] In the present disclosure, specifically, the mixed salt solution can be obtained by dissolving a soluble nickel salt, a soluble cobalt salt and a soluble manganese salt in deionized water.

[0114] According to the present disclosure, the alkaline solution and the ammonia complex solution can be selected within a certain range. For example, the alkaline solution may include a sodium hydroxide solution and / or a potassium hydroxide solution. - The concentration may be 5-10 mol / L; the ammonia complex solution may include aqueous ammonia, and the mass fraction of ammonia in the ammonia complex solution may be 15-22%.

[0115] According to the present disclosure, the reaction conditions in each stage of the reactor can vary within a certain range. For example, in the first stage reactor, the second stage reactor and the third stage reactor, the reaction temperature can be 50-65°C, the stirring speed can be 100-400 rpm, and the oxygen content can be less than 0.01% by volume.

[0116] According to the present disclosure, in order to further control the speed and progress of crystal nucleation or growth in each stage of the reactor, preferably, the effective volume of the secondary reactor can be 3-4 times the effective volume of the primary reactor, and the effective volume of the tertiary reactor can be 3-4 times the effective volume of the secondary reactor.

[0117] According to one embodiment of the present disclosure, the method further includes:

[0118] S05. Separating the particles having a particle size of 9-11 μm at D50 in the three-stage reactor, and then washing the particles;

[0119] Specifically, the particles are sent to a washing machine and washed with deionized water, alkaline solution and deionized water in sequence until the pH value of the washing liquid is ≤8.0; the washed particles are dried at 100-150°C for 5-12h to obtain a nickel-cobalt-manganese ternary precursor; the alkaline solution can be, for example, a sodium hydroxide solution with a mass fraction of 1-2%.

[0120] The second aspect of the present disclosure provides a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method described in the first aspect of the present disclosure.

[0121] According to one embodiment of the present disclosure, the quaternary material is a particle including a core and a shell layer coated outside the core.

[0122] The quaternary material disclosed in the present invention has a core-shell structure, wherein the core is formed by the agglomeration of primary particles, and the shell is formed by the arrangement of primary particles and has a "radial" structure, with a small diameter distance and a concentrated particle size distribution, which makes it easier to react with oxygen during the solid-phase reaction, and the resulting crystal structure is more complete, which alleviates the intercrystalline stress caused by volume deformation during the charge and discharge process; there are also fewer microcracks caused by multiple cyclic phase changes, which further improves the cycle performance of the battery.

[0123] According to one embodiment of the present disclosure, the particle size of the inner core is 2-4 μm, and the thickness of the shell is 1-6 μm.

[0124] According to one embodiment of the present disclosure, the diameter distance of the particles is less than 0.67, and the quaternary material having the above diameter distance can further improve the cycle stability of the battery.

[0125] According to one embodiment of the present disclosure, the D50 particle size is 9-11 μm.

[0126] In the present disclosure, particles may have a spherical and / or spheroidal morphology, and the definitions of "spherical" and "spheroidal" are conventional in the art.

[0127] According to one embodiment of the present disclosure, A Nb With D Nb The ratio is 0.9-1.1, preferably 0.95-1.05; A P With D P The ratio is 5-15, preferably 6-10; based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus on the surface of the particles, A Nb represents the molar ratio of niobium element on the surface of the particle, A P represents the molar ratio of phosphorus on the surface of the particle; based on the total molar ratio of nickel, cobalt, manganese, aluminum, niobium and phosphorus in the bulk phase of the particle, D Nbrepresents the molar ratio of niobium element in the bulk phase of the particle, D P It represents the molar proportion of phosphorus in the bulk phase of the particles; the niobium element of the material within the above range is uniformly distributed in the bulk phase, which further optimizes the crystal structure of the material, can inhibit the structural distortion and structural collapse of the material during the charge and discharge process, and improve the cycle stability; the phosphorus element is enriched on the surface of the material, which alleviates the corrosion of the electrolyte to the material, and finally realizes the effective improvement of the electrochemical cycle stability.

[0128] In the present disclosure, “the molar proportion of niobium element on the surface of the particle” refers to the ratio of the molar number of niobium element on the surface of the particle to the total molar number of nickel element, cobalt element, manganese element, aluminum element, phosphorus element and niobium element on the surface; “the molar proportion of niobium element in the bulk phase of the particle” refers to the ratio of the molar number of niobium element in the bulk phase of the particle to the total molar number of nickel element, cobalt element, manganese element, aluminum element, phosphorus element and niobium element in the bulk phase; “the molar proportion of phosphorus element on the surface of the particle” refers to the ratio of the molar number of phosphorus element on the surface of the particle to the total molar number of nickel element, cobalt element, manganese element, aluminum element, phosphorus element and niobium element on the surface; “the molar proportion of phosphorus element in the bulk phase of the particle” refers to the ratio of the molar number of phosphorus element in the bulk phase of the particle to the total molar number of nickel element, cobalt element, manganese element, aluminum element, phosphorus element and niobium element in the bulk phase.

[0129] According to one embodiment of the present disclosure, the chemical formula of the quaternary material is LiNi x Co y Mn z Al w Nb n P m O2, 0.7<x<1, 0<y<0.2, 0<z<0.1, 0<w<0.05, 0.002<n<0.02, 0.001<m<0.02.

[0130] A third aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material as described in the first aspect of the present disclosure.

[0131] Furthermore, the negative electrode material of the lithium ion battery may be, for example, a lithium sheet, and the electrolyte may be, for example, an alkyl carbonate solution of LiPF6. This is conventional in the art and no specific requirements are made here.

[0132] The present disclosure is further described below by way of examples, but the present disclosure is not limited thereto. The raw materials, reagents, instruments and equipment designed in the examples of the present disclosure can all be purchased unless otherwise specified.

[0133] The test method involved in the embodiments of the present disclosure is as follows:

[0134] (1) Test method and conditions of scanning electron microscope: FEIQuanta 200FEG, rated voltage of the equipment is 10 kV.

[0135] (2) The particle size and diameter distance were measured using the Mastersizer 2000 laser particle size analyzer from Malvern, UK.

[0136] (3) The element analysis of the particle surface was carried out using the ESCALab220i-XL X-ray photoelectron spectrometer from VG Scientific.

[0137] (4) The bulk element analysis of the particles was carried out using a Perkin-Elmer Optima 3300DV inductively coupled plasma (ICP) element analyzer.

[0138] (5) Chemical formula testing method: obtained based on the results of bulk element analysis.

[0139] Example 1

[0140] The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A1 was prepared by the following steps:

[0141] (1) Preparation of nickel-cobalt-aluminum ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 (referred to as NCM811):

[0142] a. According to the molar ratio of Ni:Co:Mn=8:1:1, nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate were dissolved in deionized water to prepare a mixed salt solution with a total molar concentration of metal ions of 2.0 mol / L; sodium hydroxide was dissolved in deionized water to prepare OH - An alkaline solution with a molar concentration of 6 mol / L; an ammonia solution with a NH3 mass fraction of 22% is prepared as an ammonia complexing solution;

[0143] b. Add deionized water accounting for 50% of the effective volume of the primary reactor, and then add the alkaline solution and ammonia complex solution prepared in step a as the reaction base solution, so that the NH3 concentration in the primary reactor is 4 g / L and the pH value is 11.3;

[0144] c. Under a nitrogen atmosphere and a stirring condition of 400 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the primary reactor in step b. When the primary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the primary reactor, and the clear liquid is discharged into the waste liquid tank. When the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is 4 times the effective volume of the primary reactor, the feeding is stopped, and the materials in the primary reactor are transferred to the secondary reactor;

[0145] The effective volume of the secondary reactor is 4 times that of the primary reactor. The reaction temperature in the primary reactor is 60°C. Before the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 11.3 and the NH3 concentration at 4g / L. After the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 10.8 and the NH3 concentration at 3.5g / L.

[0146] d. Under a nitrogen atmosphere and a stirring condition of 300 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the secondary reactor in step c. When the secondary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the secondary reactor, and the clear liquid is discharged into the waste liquid tank. When the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is 3 times the effective volume of the secondary reactor, the feeding is stopped, and the materials in the secondary reactor are transferred to the tertiary reactor;

[0147] The effective volume of the tertiary reactor is three times that of the secondary reactor. The reaction temperature in the secondary reactor is 60°C. The flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the secondary reactor at 10.8 and the NH3 concentration at 3g / L.

[0148] e. Under a nitrogen atmosphere and a stirring condition of 200 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the tertiary reactor in step d. When the tertiary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the tertiary reactor, and the clear solution is discharged into the waste liquid tank. When the D50 particle size of the particles in the tertiary reactor reaches 9 μm, the feeding is stopped;

[0149] The reaction temperature in the third-stage reactor was 60°C, and the flow rates of the alkaline solution and the ammonia complex solution were controlled to maintain the pH value in the third-stage reactor at 10.8 and the NH3 concentration at 3 g / L;

[0150] The oxygen content in the first-stage reactor, the second-stage reactor and the third-stage reactor is less than 0.01% by volume;

[0151] f. After the feeding is stopped in step e, the materials in the three-stage reactor are sequentially washed with water, alkali washed, and washed with water until the pH of the washing solution is ≤8.0, wherein the alkali solution used for alkali washing is a sodium hydroxide solution with a mass percentage concentration of 1%, and the alkali washing time is 2h;

[0152] g. Put the washed material in step f into an oven, dry it at 100° C. for 12 h, and then pass it through a 200-mesh sieve to obtain a ternary precursor of lithium nickel cobalt manganese oxide (Ni 0.8 Co 0.1 Mn 0.1 (OH)2).

[0153] (2) dissolving cobalt sulfate calculated as Co element and aluminum sulfate calculated as Al element in a molar ratio of 3:1 in deionized water to prepare a first solution with a total metal ion concentration of 1.0 mol / L;

[0154] Prepare an alkaline solution with a sodium hydroxide concentration of 1.6 mol / L and a sodium carbonate concentration of 0.25 mol / L;

[0155] The first solution and the alkaline solution were added into a colloid mill at a volume ratio of 1:1 and mixed for 3 minutes at a speed of 3000 r / min to obtain cobalt aluminum hydrotalcite Co6Al2(OH) 16 CO3·6H2O suspension;

[0156] The NCM811 precursor, the suspension containing cobalt aluminum hydrotalcite (in terms of solid phase), and nano niobium pentoxide (with an average particle size of 50 nm) were weighed and mixed in a molar ratio of 100:1:0.5, stirred and aged in a 98°C water bath for 3 hours, and then washed and filtered repeatedly until the pH of the filtrate was below 7.5, and the washed filter cake was dried at 120°C for 10 hours to obtain a first pre-product;

[0157] (3) The above pre-product and micro powder lithium hydroxide (average particle size of 7 μm) were weighed and mixed for 2.5 h according to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.06, and then the temperature was raised to 350°C at a temperature rate of 2°C / min in an oxygen atmosphere, and the mixture was calcined at a constant temperature for 3 h. The temperature was then raised to 480°C at a temperature rate of 2°C / min, and the mixture was calcined at a constant temperature for 3 h. The temperature was then raised to 750°C at a temperature rate of 4°C / min, and the mixture was calcined at a constant temperature for 15 h. Finally, the temperature was lowered to 350°C at a temperature rate of 2°C / min, and the mixture was then cooled to room temperature in the furnace to obtain a second pre-product;

[0158] The second pre-product and diammonium hydrogen phosphate (average particle size of 5 μm) were weighed at a molar ratio of 100:1, and a second ball milling was performed for 1.5 hours to obtain a third pre-product;

[0159] The third pre-product and sodium hypophosphite are weighed in a molar ratio of 20:1, the sodium hypophosphite is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace, and a second heat treatment is performed under a nitrogen atmosphere by roasting for 2 hours at a temperature of 300° C. After cooling to room temperature, the pre-product is added into water and stirred for washing for 10 minutes, and then filtered and dried to obtain a fourth pre-product;

[0160] The fourth pre-product was subjected to a third heat treatment in an oxygen atmosphere at 750°C for 5 hours by roasting to obtain a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A1 having a chemical formula of LiNi 0.726 Co 0.145 Mn 0.091 Al 0.018 Nb 0.009 P 0.011 O2, whose parameters are listed in Table 1;

[0161] The quaternary material A1 was tested by scanning electron microscope, and the results are as follows Figure 1 shown.

[0162] Example 2

[0163] The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A2 was prepared by the following method:

[0164] (1) Preparation of nickel-cobalt-manganese ternary precursor Ni 0.9 Co 0.05 Mn 0.05 (OH)2 (referred to as NCM9055):

[0165] a. According to the molar ratio of Ni:Co:Mn=9:0.5:0.5, nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate were dissolved in deionized water to prepare a mixed salt solution with a total molar concentration of metal ions of 1.8 mol / L; sodium hydroxide was dissolved in deionized water to prepare OH - An alkaline solution with a molar concentration of 7 mol / L; an ammonia solution with a NH3 mass fraction of 20% is prepared as an ammonia complexing solution;

[0166] b. Add deionized water accounting for 50% of the effective volume of the primary reactor, and then add the alkaline solution and ammonia complex solution prepared in step a as the reaction base solution, so that the NH3 concentration in the primary reactor is 4.5 g / L and the pH value is 11.4;

[0167] c. Under a nitrogen atmosphere and a stirring condition of 350 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the primary reactor in step b. When the primary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the primary reactor, and the clear liquid is discharged into the waste liquid tank. When the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is 3 times the effective volume of the primary reactor, the feeding is stopped, and the materials in the primary reactor are transferred to the secondary reactor;

[0168] The effective volume of the secondary reactor is three times that of the primary reactor. The reaction temperature in the primary reactor is 60°C. Before the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 11.4 and the NH3 concentration at 4.5 g / L. After the concentration treatment begins, the flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the primary reactor at 10.8 and the NH3 concentration at 3.5 g / L.

[0169] d. Under a nitrogen atmosphere and a stirring condition of 300 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the secondary reactor in step c. When the secondary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the secondary reactor, and the clear solution is discharged into the waste liquid tank until the total volume of the added mixed salt solution, alkaline solution and ammonia complex solution is twice the effective volume of the secondary reactor, then the feeding is stopped, and the materials in the secondary reactor are transferred to the tertiary reactor;

[0170] The effective volume of the tertiary reactor is twice that of the secondary reactor. The reaction temperature in the secondary reactor is 60°C. The flow rates of the alkaline solution and the ammonia complex solution are controlled to maintain the pH value in the secondary reactor at 10.8 and the NH3 concentration at 3g / L.

[0171] e. Under a nitrogen atmosphere and a stirring condition of 200 rpm, the mixed salt solution, alkaline solution and ammonia complex solution prepared in step a are continuously and concurrently flowed into the tertiary reactor in step d. When the tertiary reactor is full, the diaphragm pump and the concentrator are started to concentrate the materials therein, the concentrated solution is refluxed into the tertiary reactor, and the clear solution is discharged into the waste liquid tank. When the D50 particle size of the particles in the tertiary reactor reaches 9 μm, the feeding is stopped;

[0172] The reaction temperature in the third-stage reactor was 60°C, and the flow rates of the alkaline solution and the ammonia complex solution were controlled to maintain the pH value in the third-stage reactor at 10.8 and the NH3 concentration at 3 g / L;

[0173] The oxygen content in the first-stage reactor, the second-stage reactor and the third-stage reactor is less than 0.01% by volume;

[0174] f. After the feeding is stopped in step e, the materials in the three-stage reactor are sequentially washed with water, alkali washed, and washed with water until the pH of the washing liquid is ≤8.0, wherein the alkali solution used for alkali washing is a sodium hydroxide solution with a mass percentage concentration of 1%, and the alkali washing time is 1h;

[0175] g. Put the washed material in step f into an oven, dry it at 120° C. for 10 h, and then pass it through a 200-mesh sieve to obtain a ternary precursor of lithium nickel cobalt manganese oxide (Ni 0.9 Co 0.05 Mn 0.05 (OH)2);

[0176] (2) dissolving cobalt chloride calculated as Co element and aluminum chloride calculated as Al element in a molar ratio of 2:1 in deionized water to prepare a first solution with a total metal ion concentration of 0.5 mol / L;

[0177] Prepare an alkaline solution with a sodium hydroxide concentration of 1.0 mol / L and a sodium carbonate concentration of 0.5 mol / L;

[0178] The first solution and the alkaline solution were added into a colloid mill at a volume ratio of 1:1 and mixed for 3 minutes at a speed of 3000 r / min to obtain cobalt aluminum hydrotalcite Co4Al2(OH) 12 CO3·6H2O suspension;

[0179] The NCM811 precursor, the suspension containing cobalt aluminum hydrotalcite (in terms of solid phase), and nano niobium pentoxide (average particle size of 50 nm) were weighed and mixed in a molar ratio of 100:1:1, stirred and aged in a 98°C water bath for 3 hours, then washed and filtered repeatedly until the pH of the filtrate was below 7.5, and the washed filter cake was dried at 120°C for 10 hours to obtain a first pre-product;

[0180] (3) The above pre-product and micro powder lithium hydroxide (average particle size of 7 μm) were weighed and mixed for 2.5 h according to the molar ratio of n(Ni+Co+Mn+Al+Nb):n(Li)=1:1.05, and then the temperature was raised to 350°C at a temperature rate of 4°C / min in an oxygen atmosphere, and the mixture was calcined at a constant temperature for 3 h. The temperature was then raised to 500°C at a temperature rate of 4°C / min, and the mixture was calcined at a constant temperature for 3 h. The temperature was then raised to 720°C at a temperature rate of 4°C / min, and the mixture was calcined at a constant temperature for 15 h. Finally, the temperature was lowered to 350°C at a temperature rate of 2°C / min, and the mixture was then cooled to room temperature in the furnace to obtain a second product.

[0181] The second pre-product and diammonium hydrogen phosphate (average particle size of 5 μm) were weighed at a molar ratio of 100:1, and a second ball milling was performed for 1.5 hours to obtain a third pre-product;

[0182] The third pre-product and sodium hypophosphite are weighed in a molar ratio of 5:1, the sodium hypophosphite is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace, and a second heat treatment is performed under a nitrogen atmosphere by roasting for 2 hours at a temperature of 300° C. After cooling to room temperature, the mixture is added into water and stirred for washing for 10 minutes, and then filtered and dried to obtain a fourth pre-product;

[0183] The fourth pre-product was subjected to a third heat treatment in an oxygen atmosphere at 700°C for 4 hours by roasting to obtain a niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A2 having a chemical formula of LiNi 0.820 Co 0.082 Mn 0.045 Al 0.019 Nb 0.019 P 0.015 O2, its parameters are listed in Table 1.

[0184] Example 3

[0185] The method of Example 1 is used to prepare the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material A3, except that:

[0186] (2) dissolving nickel sulfate calculated as Ni element and aluminum sulfate calculated as Al element in a molar ratio of 3:1 in deionized water to prepare a first solution with a total metal ion concentration of 1.0 mol / L;

[0187] Prepare an alkaline solution with a sodium hydroxide concentration of 1.6 mol / L and a sodium carbonate concentration of 0.25 mol / L;

[0188] The first solution and the alkaline solution were added into a colloid mill at a volume ratio of 1:1 and mixed for 3 minutes at a speed of 3000 r / min to obtain nickel aluminum hydrotalcite Ni6Al2(OH) 16 CO3·6H2O suspension;

[0189] The NCM811 precursor, the suspension containing nickel aluminum hydrotalcite (in terms of solid phase), and nano niobium pentoxide (average particle size of 50 nm) were weighed and mixed in a molar ratio of 100:1:0.5, stirred and aged in a 98°C water bath for 3 hours, and then washed and filtered repeatedly until the pH of the filtrate was below 7.5. The washed filter cake was dried at 120°C for 10 hours to obtain the first pre-product; the chemical formula of the quaternary material A3 is LiNi 0.780 Co 0.091 Mn 0.091 Al 0.018 Nb0.009 P 0.011 O2, parameters are listed in Table 1.

[0190] Comparative Example 1

[0191] The method of Example 1 is used to prepare the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D1, except that:

[0192] In step (1) b, the NH3 concentration in the primary reactor is 3 g / L and the pH value is 11.0;

[0193] In step (1) c, before the concentration treatment is started, the pH value in the primary reactor is 11.0 and the NH3 concentration is 3 g / L; after the concentration treatment is started, the pH value in the primary reactor is 10.6 and the NH3 concentration is 3 g / L;

[0194] In step (1) d, the pH value in the secondary reactor is 10.6 and the NH3 concentration is 2.5 g / L;

[0195] In step (1) e, the pH value in the third-stage reactor is 10.6 and the NH3 concentration is 2.5 g / L;

[0196] Finally, the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D1 was obtained, with the chemical formula LiNi 0.726 Co 0.145 Mn 0.09 1Al 0.018 Nb 0.009 P 0.011 O2, its parameters are listed in Table 1.

[0197] Comparative Example 2

[0198] The method of Example 2 is used to prepare the niobium-phosphorus doped nickel-cobalt-manganese-aluminum lithium quaternary material D2, except that:

[0199] In step (1) b, the NH3 concentration in the primary reactor is 4 g / L and the pH value is 11.3;

[0200] In step (1) c, before the concentration treatment is started, the pH value in the primary reactor is 11.2 and the NH3 concentration is 3.5 g / L; after the concentration treatment is started, the pH value in the primary reactor is 10.5 and the NH3 concentration is 2.6 g / L;

[0201] In step (1) d, the pH value in the secondary reactor is 10.5 and the NH3 concentration is 2.6 g / L;

[0202] In step (1) e, the pH value in the third-stage reactor is 10.5 and the NH3 concentration is 2.6 g / L;

[0203] Finally, the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D2 was obtained, with the chemical formula LiNi 0.820 Co 0.082 Mn 0.04 5Al 0.019 Nb 0.019 P 0.015 O2, its parameters are listed in Table 1.

[0204] Comparative Example 3

[0205] The method of Example 1 is used to prepare the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D3, except that:

[0206] In step (1) b, the pH value in the primary reactor is 11.0;

[0207] The chemical formula of the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D3 is LiNi 0.726 Co 0.145 Mn 0.091 Al 0.018 Nb 0.009 P 0.011 O2, parameters are listed in Table 1.

[0208] Comparative Example 4

[0209] The method of Example 1 is used to prepare the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D4, except that:

[0210] In step (1) c, before starting the concentration treatment, the NH3 concentration in the primary reactor is 3.0 g / L;

[0211] The chemical formula of the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D4 is LiNi 0.726 Co 0.145 Mn 0.091 Al 0.018 Nb 0.009 P 0.011 O2, parameters are listed in Table 1.

[0212] Comparative Example 5

[0213] The method of Example 3 is used to prepare the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material D5, except that:

[0214] In step (1) b, the NH3 concentration in the primary reactor is 3 g / L and the pH value is 11.0;

[0215] In step (1) c, before the concentration treatment is started, the pH value in the primary reactor is 11.0 and the NH3 concentration is 3 g / L; after the concentration treatment is started, the pH value in the primary reactor is 10.6 and the NH3 concentration is 3 g / L;

[0216] In step (1) d, the pH value in the secondary reactor is 10.6 and the NH3 concentration is 2.5 g / L;

[0217] In step (1)e, the pH value in the three-stage reactor is 10.6, and the NH3 concentration is 2.5 g / L; the chemical formula of the quaternary material D5 is LiNi 0.780 Co 0.091 Mn 0.091 Al 0.018 Nb 0.009 P 0.011 O2, parameters are listed in Table 1.

[0218] Comparative Example 6

[0219] The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary material D6 was prepared by the method of Example 1, except that commercially available Ni 0.8 Co 0.1 Mn 0.1 (OH)2 ternary precursor is used as nickel-cobalt-manganese precursor, and the chemical formula of quaternary material D6 is LiNi 0.726 Co 0.145 Mn 0.091 Al 0.018 Nb 0.009 P 0.011 O2, parameters are listed in Table 1;

[0220] The quaternary material D6 was tested by scanning electron microscope, and the results are as follows Figure 2 As shown;

[0221] according to Figure 2 It can be seen that the commercially available Ni 0.8 Co 0.1 Mn 0.1 The quaternary material prepared by using the (OH)2 ternary precursor as a nickel-cobalt-manganese precursor has no primary particle core, that is, no core-shell structure.

[0222] Comparative Example 7

[0223] The quaternary material D7 is prepared by the method of Example 1, except that in step (2), no nano niobium pentoxide is added. The chemical formula of the quaternary material D7 is LiNi 0.733 Co 0.147 Mn 0.091 Al 0.018 P 0.011 O2, parameters are listed in Table 1.

[0224] Table 1

[0225] Example / Comparative Example <![CDATA[A Nb With D Nb Ratio of]]> <![CDATA[A P With D P Ratio of]]> Span Example 1 1.013 6.17 0.643 Example 2 1.009 9.25 0.656 Example 3 1.016 6.34 0.664 Comparative Example 1 1.021 6.20 0.696 Comparative Example 2 1.011 9.33 0.687 Comparative Example 3 1.015 6.36 0.701 Comparative Example 4 1.020 6.28 0.694 Comparative Example 5 1.025 6.42 0.692 Comparative Example 6 1.010 6.26 1.268 Comparative Example 7 - 6.38 0.649

[0226] As can be seen from Table 1, based on the comparison between Examples 1-3 and Comparative Examples 1-6, the element proportions of Nb element in the surface layer and the bulk phase of the niobium-phosphorus co-doped nickel cobalt manganese aluminum oxide quaternary material prepared by the method of the present invention are basically the same, while the element proportion of P element on the surface is significantly higher than that in the bulk phase, indicating that the method of the present invention can prepare niobium-phosphorus co-doped nickel cobalt manganese aluminum oxide quaternary materials with uniform Nb element distribution and P element enriched on the surface; at the same time, the niobium element doped nickel cobalt manganese aluminum oxide quaternary materials A1-A3 prepared by the method of the present invention have smaller diameters than those of Comparative Examples D1-D7, and the particle size distribution is more concentrated.

[0227] according to Figure 1 and Figure 2 In comparison, A1 prepared by the method disclosed in the present invention has a core-shell structure with obvious differences in internal and external appearance, while D6 prepared using commercially available precursors has an ordinary scattered profile without a core-shell structure.

[0228] Test Example 1-10

[0229] The quaternary materials of Examples 1-3 and Comparative Examples 1-7 were used as positive electrode materials, mixed with acetylene black conductive agent and polyvinylidene fluoride binder in a mass ratio of 94:3:3, coated on the surface of aluminum foil current collector, dried at 110°C and pressed into sheets, and electrode sheets with a diameter of 1 cm were obtained by a punching machine. The sheets were vacuum dried in a vacuum oven at 120°C for 24 h as positive electrodes, metal lithium sheets were used as negative electrodes, polyethylene films were used as separators, 1 mol / L LiPF6 / (ethylene carbonate + dimethyl carbonate) was used as electrolyte, wherein the volume ratio of ethylene carbonate to dimethyl carbonate was 1:1, and button batteries were assembled in a glove box.

[0230] The Wuhan Blue Electric CT2001A battery tester was used to test the electrochemical performance, and the charge and discharge voltage range was 2.7-4.3V (vs.Li + / Li). After 5 cycles of charge and discharge at 0.1C, 3 cycles of charge and discharge at 0.2C were performed, and finally a long-term cycle at 0.5C was performed. The results are listed in Table 2.

[0231] Table 2

[0232]

[0233]

[0234] According to the data in Tables 1 and 2, the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary materials A1-A3 prepared by the method disclosed in the present invention have better capacity retention rates after 200 cycles than materials D1-D7, indicating that the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum quaternary materials prepared by the method disclosed in the present invention have better electrochemical properties.

[0235] Specifically, according to the data comparison of materials A1-A3 and D6, the niobium-phosphorus co-doped nickel cobalt manganese aluminum oxide prepared from the nickel-cobalt-manganese ternary precursor prepared by the specific method of the present invention has a core-shell structure, and the capacity retention rate and first discharge capacity of the material are significantly better than those of the material prepared by the commercially available precursor; according to the comparison of A1-A3 and D1-D5, it can be seen that the particle size distribution of the material prepared by the method of the present invention is more concentrated, and the migration path and deintercalation degree of lithium ions of the material with more uniform particle size during long-term cycling are also more consistent, which is more conducive to maintaining a lower capacity loss and further improving the cycle stability of the material.

[0236] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0237] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0238] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A method for preparing niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum-lithium quaternary material, characterized in that: The method comprises the following steps: (1) contacting a suspension containing aluminum-based hydrotalcite, a nickel-cobalt-manganese ternary precursor and a niobium-containing compound to react and obtain a first pre-product; (2) subjecting the first pre-product and the lithium-containing compound to a first ball milling, and then subjecting the obtained mixture to a first heat treatment in a first oxygen-containing atmosphere to obtain a second pre-product; (3) subjecting the second pre-product and the first phosphorus-containing compound to a second ball milling; (4) subjecting the third pre-product obtained in step (3) and the second phosphorus-containing compound to a second heat treatment under an inert atmosphere; (5) subjecting the fourth pre-product obtained in step (4) to a third heat treatment in a second oxygen-containing atmosphere; Wherein, the aluminum-based hydrotalcite contains a transition metal element, the transition metal element is a cobalt element or a nickel element, and the molar ratio of the transition metal element to the aluminum element is (2-5):1; The method for preparing the nickel-cobalt-manganese ternary precursor comprises the following steps: S01. Adding a reaction base liquid to a primary reactor, wherein the reaction base liquid comprises water, an alkaline solution and an ammonia complexing liquid, and the amount of the reaction base liquid added is 30%-80% of the effective volume of the primary reactor; S02. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the primary reactor, and when the primary reactor is full, the material in the primary reactor is concentrated, and the concentrated solution is refluxed into the primary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 3-4 times the effective volume of the primary reactor, and the material in the primary reactor is transferred to the secondary reactor; S03. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, alkaline solution and ammonia complex solution are continuously introduced into the secondary reactor, and when the secondary reactor is full, the material in the secondary reactor is concentrated, and the concentrated solution is refluxed into the secondary reactor until the total amount of the mixed salt solution, alkaline solution and ammonia complex solution added is 2-3 times the effective volume of the secondary reactor, and the material in the secondary reactor is transferred into the tertiary reactor; S04. Under nitrogen atmosphere and stirring conditions, the mixed salt solution, the alkaline solution and the ammonia complex solution are continuously introduced into the tertiary reactor, and when the tertiary reactor is full, the material in the tertiary reactor is concentrated, and the concentrated solution is refluxed into the tertiary reactor until the D50 particle size of the particles in the tertiary reactor is 9-11 μm; In step S01, when adding the reaction base solution, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-5 g / L; In step S02, before the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 11.3-11.5 and the NH3 concentration is 3.5-4.5 g / L; after the material in the primary reactor is concentrated, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the primary reactor is 10.7-11.0 and the NH3 concentration is 3-4 g / L; In step S03, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the secondary reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L; In step S04, the flow rates of the alkaline solution and the ammonia complex solution are controlled so that the pH value in the three-stage reactor is 10.7-11.0 and the NH3 concentration is 3-3.5 g / L.

2. The method according to claim 1, wherein: The chemical formula of the nickel-cobalt-manganese ternary precursor is Ni 1-a-b Co a Mn b (OH)2, where 0 <a≤0.1,0<b≤0.1。 3. The method according to claim 1, wherein: In step (1), the molar ratio of the transition metal element in the aluminum-based hydrotalcite to the niobium element in the niobium-containing compound is 2:1 or more.

4. The method according to claim 1, wherein: The niobium-containing compound includes one or more of niobium pentoxide, niobium oxalate and ammonium niobium oxalate; The lithium-containing compound includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate; The first phosphorus-containing compound includes one or more of ammonium phosphate, diammonium hydrogen phosphate and diammonium dihydrogen phosphate; The second phosphorus-containing compound includes phosphite and / or hypophosphite; Optionally, the phosphite includes sodium phosphite and / or ammonium phosphite, and the hypophosphite includes sodium hypophosphite and / or ammonium hypophosphite; The molar ratio of the first phosphorus-containing compound to the second pre-product is (0.5-4):100; The molar ratio of the second phosphorus-containing compound to the third pre-product is 1:(2-50).

5. The method according to claim 1, wherein: The average particle size of the niobium-containing compound is 50-80 nm, the average particle size of the lithium-containing compound is 6-8 μm, and the average particle size of the first phosphorus-containing compound is 5-10 μm.

6. The method according to claim 1, wherein: The molar ratio of the total molar sum of nickel element, cobalt element, manganese element, aluminum element and niobium element in the first pre-product to the molar ratio of the lithium element in the lithium-containing compound is 1:(1.0-1.1).

7. The method according to claim 1, wherein: In step (2), the first heat treatment comprises the following steps: a. Raise the temperature to 300-400°C at a heating rate of 1-8°C / min for the first calcination for 1-3h; b. Continue heating to 450-500°C at a heating rate of 1-8°C / min and perform a second calcination for 1-3h; c. Continue heating to 700-800°C at a heating rate of 2-6°C / min for the third calcination for 10-15h; d. Cool down to 300-400℃ at a cooling rate of 1-3℃ / min, and then cool to below 100℃.

8. The method according to claim 1, wherein: Step (4) is carried out in a tube furnace, the second phosphorus-containing compound is placed upstream of the tube furnace, and the third pre-product is placed downstream of the tube furnace.

9. The method according to claim 1, wherein: In step (4), the second heat treatment method includes calcination, and the second heat treatment conditions include a temperature of 200-400° C. and a time of 1-5 h; In step (5), the third heat treatment method includes roasting, and the third heat treatment conditions include: temperature of 600-850°C and time of 3-8h.

10. The method according to claim 1, wherein: The inert atmosphere includes nitrogen atmosphere and / or argon atmosphere; The first oxygen-containing atmosphere and the second oxygen-containing atmosphere are the same or different, and are independently an oxygen atmosphere or an air atmosphere.

11. The method according to claim 1, wherein: The time for the first ball milling and the second ball milling is 1-4 hours respectively.

12. The method according to claim 1, wherein: The mixed salt solution contains nickel ions, cobalt ions and manganese ions, and the total molar concentration of the nickel ions, the cobalt ions and the manganese ions is 1.8-2.5 mol / L.

13. The method according to claim 1, wherein: The alkaline solution comprises a sodium hydroxide solution and / or a potassium hydroxide solution. - The concentration is 5-10 mol / L; The ammonia complex solution includes aqueous ammonia, and the mass fraction of NH3 in the ammonia complex solution is 15-22%.

14. The method according to claim 1, wherein: In the primary reactor, the secondary reactor and the tertiary reactor, the reaction temperature is 50-65° C., the stirring speed is 100-400 rpm, and the oxygen content is less than 0.01% by volume.

15. The method according to claim 1, wherein: The effective volume of the secondary reactor is 3-4 times that of the primary reactor, and the effective volume of the tertiary reactor is 3-4 times that of the secondary reactor.

16. Niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method described in any one of claims 1 to 15.

17. The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material according to claim 16, wherein: The quaternary material is a particle including a core and a shell layer coated outside the core; The diameter distance of the particles is less than 0.

67.

18. The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material according to claim 16, wherein: A Nb With D Nb The ratio is 0.9-1.1, A P With D P The ratio is 5-15; Based on the total molar amount of nickel, cobalt, manganese, aluminum, niobium and phosphorus on the surface of the particles, A Nb represents the molar ratio of niobium element on the surface of the particle, A P represents the molar percentage of phosphorus on the surface of the particle; Based on the total molar mass of nickel, cobalt, manganese, aluminum, niobium and phosphorus in the bulk phase of the particles, D Nb represents the molar ratio of niobium element in the bulk phase of the particle, D P It represents the molar percentage of phosphorus element in the bulk phase of the particles.

19. The niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material according to claim 16, wherein: The quaternary material includes a chemical formula of LiNi x Co y Mn z Al w Nb n P m Particles of O2, 0.7<x<1, 0<y<0.2, 0<z<0.1, 0<w<0.05, 0.002<n<0.02, 0.001<m<0.

02.

20. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the niobium-phosphorus co-doped nickel-cobalt-manganese-aluminum lithium quaternary material according to any one of claims 16-19.

Citation Information

Patent Citations

  • Niobium-phosphorus co-doped high nickel ternary positive electrode material and preparation method and application thereof

    CN110085858A